Creativity and resilience as predictors of career success - Fernández-Díaz, J.R.; Gutiérrez-Ortega, Mónica; Llamas-Salguero, F.; Cantón-Mayo, I. (MDPI, 2021)
Achieving success in today’s society is becoming an increasingly complex endeavor. People must have high levels of creativity and resilience in order to constantly adapt to changing situations and, at the same time, maintain the necessary tenacity and enthusiasm to continue despite failures. This research aims to identify the different characteristics of people with high levels of objective career success, subjective career success, resilience, and creativity, and analyze their relationship with the achievement of career success. The sample consisted of 200 people from six professional categories (unemployed, managers, influencers, entrepreneurs, employees, and professors) in Spain. The questionnaire (EX. P/RE/CRE—professional success, resilience, and creativity) that was designed for this study was used to collect the data. The results suggest that a person with high levels of creativity and/or resilience is more prepared to achieve professional success from both an objective and subjective perspective. The study’s conclusions support the correlations between the terms and describe the characteristics and conditions of the successful, resilient, and/or creative person.
Keywords: subjective career success; objective career success; resilience; creativity; WOS(2); Scopus